BISTFaSC: An Approach to Embed Structural Testing Facilities into Software Components - Eler, Marcelo Medeiros; Masiero, Paulo Cesar (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2013: Anais do VII Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2013)
Component-based applications can be composed by in-house or COTS (Commercial off-the-shelf) components. In many situations, reused components should be tested before their integration into an operational environment. Testing components is not an easy task because they are usually provided as black boxes and have low testability. Built-in Testing (BIT) is an approach devised to improve component testability by embedding testing facilities into software components usually to support specification-based testing.Such components are called testable components. There are situations, however, in which combining specification and program-based testing is desirable. This paper proposes a BIT technique designed to introduce testing facilities into software components at the provider side to support structural testing at the user side, even when the source code is unavailable. An implementation to generate testable components written in Java is also presented. The approach was firstly evaluated by an exploratory study conducted to transform COTS components into testable components.